1976
DOI: 10.1080/14640747608400553
|View full text |Cite
|
Sign up to set email alerts
|

The Perception and Identification of Mirror-Reversed Patterns

Abstract: Many species have difficulty in discriminating between mirror-image stimuli, especially those about a vertical axis, and when identificatory rather than purely perceptual processes are involved. Various theories are reviewed. In two experiments involving same-different judgments for pairs of stimuli, triangles or semicircles, these were simultaneously presented either unilaterally or bilaterally, and in mirror or aligned orientations with respect to each other. Mirror oriented stimuli presented to opposite cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 87 publications
4
16
0
Order By: Relevance
“…For example, rotations through angles close to 90' can greatly reduce recognisability, although this effect is much less for rotations through 180' and for reflections (Dearborn, 1899;Rock, 1973;Foster, 1978 (Attneave, 1950), discrimination of mirror images (Sekuler and Rosenblith, 1964;Sekuler and Pierce, 1973), and identification of parafoveal figure pairs (Banks, Bachrach and Larson, 1977;Banks, Larson and Prinzmetal, 1979;Chastain and Lawson, 1979), have all been shown to depend on the relative positions of the stimuli. Also the time taken to report sameness of mirror pairs has been found to be shorter when the patterns are presented symmetrically about the point of fixation than when they are both presented to one side (Corballis and Roldan, 1974;Bradshaw, Bradley and Patterson, 1976). Similarly, it has been demonstrated that symmetry in a complex random-dot pattern is best perceived when the observer fixates a point on the axis of symmetry (Julesz, 1971; Barlow and Reeves, 1979; see also Bruce and Morgan, 1975).…”
Section: Introductionmentioning
confidence: 91%
“…For example, rotations through angles close to 90' can greatly reduce recognisability, although this effect is much less for rotations through 180' and for reflections (Dearborn, 1899;Rock, 1973;Foster, 1978 (Attneave, 1950), discrimination of mirror images (Sekuler and Rosenblith, 1964;Sekuler and Pierce, 1973), and identification of parafoveal figure pairs (Banks, Bachrach and Larson, 1977;Banks, Larson and Prinzmetal, 1979;Chastain and Lawson, 1979), have all been shown to depend on the relative positions of the stimuli. Also the time taken to report sameness of mirror pairs has been found to be shorter when the patterns are presented symmetrically about the point of fixation than when they are both presented to one side (Corballis and Roldan, 1974;Bradshaw, Bradley and Patterson, 1976). Similarly, it has been demonstrated that symmetry in a complex random-dot pattern is best perceived when the observer fixates a point on the axis of symmetry (Julesz, 1971; Barlow and Reeves, 1979; see also Bruce and Morgan, 1975).…”
Section: Introductionmentioning
confidence: 91%
“…This is a remarkable resolution and very close to the two-point threshold for fields comprising identical point-pairs (approximately 2 min of arc). Therefore, this process is probably the same as that which Mach (1886) considered so important to the problem of form vision, and which has been investigated subsequently using a wide variety of stimuli, such as geometric shapes and letters (e.g., Bradshaw, Bradley, & Patterson, 1976;Corballis, Miller, & Morgan, 1971;Sekuler & Pierce, 1973;Staller & Sekuler, 1977).…”
Section: Colllnearity Of Midpointsmentioning
confidence: 98%
“…It is also possible that the information concerning relative orientational sensitivity is biased in many previous studies (see Bradshaw, Bradley, & Patterson, 1976, for a complete discussion of problems in this regard). In the experiments reported here, the sensitivity of each orientation was measured independently of every other orientation, with each being compared to a null stimulus, an equally dense uncorrelated dynamic dot texture.…”
mentioning
confidence: 99%